The power of anime: using anime for education and outreach in STEM - Gomez, Roman G.; Tringali, Billy; Baker, Caleb; Stone, Kristjan (Frontiers in Education, 2025)
Anime is a powerful tool for science education and outreach, thanks to its popularity among younger generations and its greater accessibility. Anime conventions attract patrons from diverse generational, educational, and professional backgrounds, presenting a unique opportunity for public scholarship and for generating enthusiasm for science education. Anime Expo (AX), an annual convention held around the fourth of July in Los Angeles, is the largest anime convention in the United States and one of the largest in the world. AX 2025 hosted 410,000 attendees from 65 different countries. This event features a 3-days symposium of academic panels from the Journal of Anime and Manga Studies (JAMS). This work demonstrates that anime is a powerful tool for science education and outreach. The introduction discusses anime’s tangible effects on global protest movements and the monetary and social impact of anime conventions on attendees and their hosting cities. The body of our work discusses how, for the past 3 years, “The Physics of Anime” panel has been presented at the JAMS@AX Symposium, and the success of this panel has yielded an excellent example of public scholarship and science outreach. Pre- and post- “Physics of Anime” panel surveys administered at the AX 2025 JAMS symposium revealed a strong preference for using anime to teach Science, Technology, Engineering, and Mathematics (STEM) concepts, especially among the current target demographic (20–30-years-olds). Overall, the majority of the survey participants expressed greater comfort with the subject matter. Specific details of the survey are the subject of this work.